A STUDY ON CRYPTOCURRENCY WALLET COINSWITCH - Hamdulay, Nawaz Ali; Ponde, Sandeep J (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The traditional wallet we have been using for decades is a carry pouch on a go in which a person carries his/her fiat currency and small personal items like identification documents like a driver’s license, visiting cards, debit cards, credit cards, or any laminated cards. However, in the age of crypto currency, you need a wallet to keep your crypto tokens in one place for use on a daily basis and for trading and earning more crypto tokens so this wallet is known as crypto wallet. It enables you to store and handle all of the day’s chaos with it. This study will examine CoinSwitch a crypto currency wallet, and all the features and services it provides to its dedicated users. The impact of the CoinSwitch wallet on the Indian crypto currency market will be examined in the research article. The research article will also examine CoinSwitch’s SWOT analysis, benefits and drawbacks as a crypto currency wallet.